Severe Influenza Pneumonia Complicated with Bacterial Coinfection in a Healthy Young Man: A Case Report - Leong Hui Shan; Ker Hong Bee; Nik Nur Lisa Syahira Kaswadi (Asian Journal of Medicine & Health Sciences, 2024)
Influenza is a contagious viral respiratory infection of significant public health concern given its association with recurring global pandemics and substantial disease burden worldwide. It typically causes an abrupt-onset febrile illness with cough, rhinitis, sore throat and other constitutional symptoms. With increased awareness of vaccination and better treatment strategies, influenza is often uncomplicated and self-limiting in majority of the healthy individuals. However, there are various factors which can increase the susceptibility of the host to severe infection. This report aims to describe a case of severe influenza pneumonia in a healthy young man and to highlight a coinfection with an unexpected opportunistic microorganism, Burkholderia multivorans